Development and validation of a highly sensitive HPLC method for quantifying cardiovascular drugs in human plasma using dual detection - Khalid A. M. Attia; Ahmed H. Abdel-Monem; Ahmed M. Abdel-Raoof; Amr S. Eissa (Scientific Reports)
Abstract Cardiovascular diseases are the major cause of global mortality, and often require the concomitant use of a number of drugs to prevent and reduce these deaths. The challenge is to find effective and accurate methods for analyzing these drugs in plasma. This research introduces an innovative, sustainable HPLC-FLD method for the concurrent determination of bisoprolol (BIS), amlodipine besylate (AML), telmisartan (TEL), and atorvastatin (ATV) within human plasma. Chromatographic separation was achieved using an isocratic elution mode on a Thermo Hypersil BDS C18 column (150 × 4.6 mm, 5.0 μm), while the mobile phase comprised of ethanol and 0.03 M potassium phosphate buffer (pH 5.2) in a 40:60 ratio, with a flow rate of 0.6 mL/min. The eluate was analyzed using UV detection within the wavelength range of 210–260 nm to confirm effective separation of the four cardiovascular drugs. For enhanced specificity, a fluorescence detector was set to 227ex/298em for BIS, 294ex/365em for TEL, 274ex/378em for ATV, and 361ex/442em for amlodipine. The method was validated following the International Council for Harmonisation (ICH) guidelines. Linearity was established within the ranges of 5–100 ng/mL for BIS and AML, 0.1–5 ng/mL for TEL, and 10–200 ng/mL for ATV, ensuring accuracy and precision. The significant of the current work represented in introduction of a highly sensitive, and selective analytical method, utilizing an economical sample preparation strategy, for the simultaneous determination of four different cardiovascular drugs (bisoprolol, amlodipine, telmisartan, and atorvastatin) in spiked human plasma. The extraction of sample was carried by liquid-liquid extraction (LLE) and analyzed by LC-fluorescence detector. The chromatographic run was short (less than10 min) which is a greet economical value.